Counseling and Psychology Student Experiences of Personal Therapy: A Critical Interpretive Synthesis - Edwards, Jane (Frontiers in Psychology, 2018)
Background: Committing to attendance at personal therapy sessions is frequently either mandated or encouraged in many different types of therapeutic trainings across allied health, psychotherapy, social work and counseling. The small number of published accounts have indicated that student experiences of personal therapy can be mixed. Methods: The project examined contemporary interview based research about student experience of personal therapy during training using Critical Interpretive Synthesis method. Ten papers were found which met the search criteria. The papers included a total of 89 participants (75 F). Results: The results comprised 12 themes derived from 89 meaning units gleaned from student experiences presented in the research studies. These were used to inform a synthesizing statement here truncated as follows: Beginning therapy is challenging for some students, especially when attendance is mandatory. However, students can experience transformative change by the end of the process, even if they commence the work in a guarded way. Multiple problems can arise in the process of attending therapy as a student, and it can be difficult for a student to know what to do if these challenges are overwhelming. Attending personal therapy brings rich learnings which can be applied in clinical work but can also positively impact learning in the course, and lifelong personal development. The process can enhance the student's understanding of what the client may experience in the therapeutic journey. Conclusions: Attending personal therapy during training is not a straightforward process for all students. Course leaders and trainers need to be mindful of the possibility that students will struggle with the personal therapy requirement. Course and professional bodies should regularly review personal therapy requirements, being clear about the aims; remaining attuned to the student experience.